Acerca de la interpretación en el control de las reformas constitucionales (2007)
The main objective of this work is analyzing the interpretative activity of constitutional judges at the time they are making statements when faced with constitutional amendments. It sustains that the Supreme Court of Justice at their time, and the Constitutional Court today, combine several juridical interpretation criteria o methods when they justify the enhancement of their constitutionality control powers with respect to amendments to the Constitution, while they resort to the literal criteria while they “restrict themselves” in the face of this competence. The article refers to the interpretation, and the general interpretation criteria, and analyzes those of the Supreme Court of Justice’s jurisprudence (judgments of 1978, 1981, and 1990), and of the Supreme Court of Justice’s jurisprudence between 1992 and 2006.